Ocorrência de doenças na cultura do crambe (Crambe Hochst abyssinica) cultivado na região oeste do Paraná e efeito de Xanthomonas campestris pv. campestris na produção da cultura - Moers, éverli Marlei (2012)
Several factors indicate that petroleun must be replaced by alternative energy sources. In Brazil there are several government programs that encourage research and commercialization of renewable energy. In this context, is strengthening the productive chain of biodiesel, for which various raw materials have been tested with the aim of supplying the market in a sustainable manner. Among the alternatives is crambe, which can be an important alternative for the winter crop, considered rustic plant, drought resistant and low temperatures, with high oil content, low production cost, and that their becomes non-edible oil a good alternative for biodiesel production, since it does not compete as raw food. The culture of crambe begins to be deployed in the southern region, but little is known about plant performance and the factors that may limit their production under our environmental conditions. The objective of this study was a survey of conditions in culture, as well as evaluating the interference of the pathogen Xanthomonas campestris pv. campestris on productivity in crambe. The survey was conducted of the disease in the experimental field of FAG-Faculdade Assis Gurcacz in Cascavel / PR. The analysis of the collected material occurred in the Laboratory of Phytophatology of the UNIOESTE campus Marechal Cândido Rondon, from the observed symptoms and characteristics of the pathogen isolated. In addition, was conducted sanity of seeds in a commercial seed lot and another lot purchased directly from the producer. The interference of X. campestris in the crambe productivity was evaluated by inoculating different concentrations of bacterial suspensions, evaluating the severity for each treatment and from this calculating the AUDPC (area under disease progress curve). The yield components were correlated to the severity and AUDPC. In both seed lots were found bacteria and fungi, especially the fact that these agents may become the initial inoculum for the establishment of disease in the field. In surveying the field symptoms were observed and subsequently identified three diseases, damping off caused by Fusarium sp., Alternaria stains caused by the fungus of the genus Alternaria sp. and black rot, caused by the bacterium Xanthomonas campestris pv. campestris, the main pathogen of brassicas. Evaluating the effect of X. campestris in the production of crambe was observed linear correlation between severity and AUDPC with the total production of grain and 1000 grain weigth, so the occurrence of the disease negatively affected production of these components.